2023
DOI: 10.3389/fpubh.2022.1060700
|View full text |Cite
|
Sign up to set email alerts
|

Repair of rotator cuff tears in patients aged 75 years and older: Does it make sense? A systematic review

Abstract: BackgroundRotator cuff injuries are common, and morbidity increases with age. The asymptomatic full-thickness tear rate is 40% in the over 75-year-old population.PurposeThis study aimed to systematically review the literature on the outcomes of rotator cuff repair among >75 years old patients.Study designSystematic review.MethodsA systematic review of the literature was performed following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. A literature search was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Additionally, conditions such as hip or knee osteoarthritis [ 67 , 68 , 69 ] show a significant increase in prevalence with age. It is noteworthy that studies have reported a 40% prevalence of complete rotator cuff tears [ 70 ] and knee osteoarthritis in the population aged over 75 years.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, conditions such as hip or knee osteoarthritis [ 67 , 68 , 69 ] show a significant increase in prevalence with age. It is noteworthy that studies have reported a 40% prevalence of complete rotator cuff tears [ 70 ] and knee osteoarthritis in the population aged over 75 years.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of age on RC defects, they have been found to affect up to 70% of people over 70 [4]. Elderly patients often present multiple risk factors, including decreased bone quality, poor blood supply, and increased medical comorbidities [5]. Diabetes and other systemic disorders have also been associated with a greater risk of RC defects [6].…”
Section: Introductionmentioning
confidence: 99%
“…Outrossim, conforme estudos, as pessoas com um tipo de gordura "central" correm maior risco de saúde do que aquelas cuja gordura é distribuída. Consoante os estudos Feng 5 , o índice de obesidade em pessoas com 60 anos ou mais aumentou bastante nos últimos anos, sendo a obesidade abdominal reconhecida como fator de risco independente para o diabetes. Nota-se, também, que em indivíduos do sexo masculino, a circunferência do pescoço acima do normal foi significativamente relacionada ao aumento da prevalência de diabetes mellitus (DM).…”
Section: Introductionunclassified